Overlapping conditions in Long COVID at a multisite academic center - Grach, Stephanie L.; Dudenkov, Daniel V.; Pollack, Beth; Fairweather, DeLisa; Aakre, Chris A.; Munipalli, Bala; Croghan, Ivana T.; Mueller, Michael R.; Overgaard, Joshua D.; Bruno, Katelyn A.; Collins, Nerissa M.; Li, Zhuo; et al. (Frontiers in Neurology, 2024)
Background: Many patients experience persistent symptoms after COVID-19, a syndrome referred to as Long COVID (LC). The goal of this study was to identify novel new or worsening comorbidities self-reported in patients with LC.Methods: Patients diagnosed with LC (n=732) at the Mayo Long COVID Care Clinic in Rochester, Minnesota and Jacksonville, Florida were sent questionnaires to assess the development of new or worsening comorbidities following COVID-19 compared to patients with SARS-CoV-2 that did not develop LC (controls). Both groups were also asked questions screening for myalgic encephalomyelitis/ chronic fatigue syndrome (ME/CFS), generalized joint hypermobility (GJH) and orthostatic intolerance. 247 people with LC (33.7%) and 40 controls (50%) responded to the surveys.Results: In this study LC patients averaged 53 years of age and were predominantly White (95%) women (75%). The greatest prevalence of new or worsening comorbidities following SARS-CoV-2 infection in patients with LC vs. controls reported in this study were pain (94.4% vs. 0%, p<0.001), neurological (92.4% vs. 15.4%, p<0.001), sleep (82.8% vs. 5.3%, p<0.001), skin (69.8% vs. 0%, p<0.001), and genitourinary (60.6% vs. 25.0%, p=0.029) issues. 58% of LC patients screened positive for ME/CFS vs. 0% of controls (p<0.001), 27% positive for GJH compared to 10% of controls (p=0.026), and a positive average score of 4.0 on orthostatic intolerance vs. 0 (p<0.001). The majority of LC patients with ME/CFS were women (77%).Conclusions: We found that comorbidities across 12 surveyed categories were increased in patients following SARS-CoV-2 infection. Our data also support the overlap of LC with ME/CFS, GJH, and orthostatic intolerance. We discuss the pathophysiologic, research, and clinical implications of identifying these conditions with LC.